Turbin Air Arus Sungai Model Sudu Propeller Menggunakan Nozzel-Diffuser - Rendi Rendi; Sobar Ihsan; Syamsul Ma'arif (Proklamasi 45 University, 2020)
The application of river flow water turbines as energy sources often experiences obstacles such as the changing speed of river water flow and low turbine efficiency. This obstacle can be overcome by creating an effective and efficient river flow turbine. One way to overcome these obstacles is to add a propeller and diffuser on the turbine. This study aims to determine the value of turbine efficiency from the results of field experiments using a prototype of a river flow water turbine with a propeller blade model and to use a nozzle-diffuser. The method used is to design a river flow water turbine with propeller and diffuser, then prototype testing is carried out in the Amandit River. Data generated from field testing were analyzed to determine the value of turbine efficiency. The test results show that the prototype of a river current water turbine using a nozzle-diffuser can work well at water speeds of 0.5 m/s to 1.1 m/s. The higher the speed of the water, the higher the turbine rotation speed, the higher the torque value, and the higher the turbine power. At a water velocity of 0.5 m/s, a turbine rotation speed of 58 rpm with a torque of 0.875 N.m, while at a water speed of 1.1 m/s, a turbine rotational speed of 115 rpm with a torque of 1.250 N.m. At all water speeds and turbine speed, the turbine efficiency is fixed at 44%.